Odpowiedzi

Najlepsza Odpowiedź!
2009-11-24T16:37:15+01:00
A) 3a-3 = 3(a-1)
4+x - hym... a nie czasem 4+4x, jesli tak to 4(1+x)
6m-6a= 6(m-1)
b) 8a-16=8(a-2)
15b+10=5(3b+2)
16b-12c = 4(4b-3c)
c) 12x+36y= 12(x+3y)
y-3y = 2y... chyba, ze to mialo byc 6-3y, jesli tak to 3(2-y)
15a²+12b²= 3(5a²+4b²)
d) 24x²-16y= 8(3x²-2y)
12a²-8b= 4(3a²-2b)
10n-15m=5(2n-3m)
2009-11-24T16:41:18+01:00
A) 3a-3=3(a-1)
4+x=1(4+x)
6m-6a=6(m-a)
b) 8a-16=8(a-2)
15b+10=5(3b+2)
16b-12c=4(4b-3c)
c) 12x+36y=12(x+3y)
y-3y=y(1-3)
15a²+12b²=3(5a²+4b²)
d) 24x²-16y=4(6x²-4y)
12a²-8b=4(3a²-2b)
10n-15m=5(2n-3m)
2009-11-24T16:43:57+01:00
A) 3a-3=3(a-1)
4+x=1(4+x)
3.6m-6a=6(m-a)
b) 8a-16=8(a-2)
15b+10=5(3b+2)
16b-12c=4(4b-3c)
c) 12x+36y=12(x+3y)
y-3y=y(1-3)
15a²+12b²=3(5a²+4b²)
d) 24x²-16y=4(6x²-4y)
12a²-8b=4(3a²-2b)
10n-15m=5(2n-3m)